Specimen for a Novel Concept of Biaxial Tension Test? Design and Optimisation - Hußnätter, Wolfgang; Merklein, Marion; Geiger, Manfred (Advanced Methods in Material Forming, 2007)
Although in times of highest significance of process modelling and numerical simulation yield loci get more and more important, these characteristic values do only exist for a few materials primarily at room temperature. In this paper a novel concept of an experimental setup is introduced, with which plastic yielding of sheet metal can be examined also at elevated temperatures. The design of specimen is of great importance for the quality of experimental results, because stress conditions and with it forming behaviour are constituted. Thus, it must be optimized in consideration of stress singularities at corners and for achieving stress states, which are comparable to those of previous yield locus examinations. Most information and details can be obtained from finite element simulation. © 2007 Springer-Verlag Berlin Heidelberg.
LFT Import::2019-07-16 (1389)
Keywords: FE-simulation; sheet metal forming; yield locus